CSC780: Parallel Processing / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2015)
The course introduces the students to range of topics involved in parallel operations to improve computational performance. It explores various aspects of parallel computing including parallel architectures, parallel algorithms and parallel applications.